2021
DOI: 10.3390/ijerph18115938
|View full text |Cite
|
Sign up to set email alerts
|

Association between Maternal Origin, Pre-Pregnancy Body Mass Index and Caesarean Section: A Nation-Wide Registry Study

Abstract: Aims: To explore the association between maternal origin and birthplace, and caesarean section (CS) by pre-pregnancy body mass index (BMI) and length of residence. Methods: We linked records from 118,459 primiparous women in the Medical Birth Registry of Norway between 2013 and 2017 with data from the National Population Register. We categorized pre-pregnancy BMI (kg/m2) into underweight (<18.5), normal weight (18.5–24.9) and overweight/obese (≥25). Multinomial regression analysis estimated crude and adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(54 reference statements)
0
6
0
Order By: Relevance
“… 3 , 25 In many studies, maternal overweight and obesity were significantly associated with a higher risk of cesarean delivery, particularly in low- and middle-income countries. 3 , 20 , 28 , 29 In high-income countries (eg, Europe, Central Asia, and South Asia), a BMI ≥ 25 kg/m 2 was associated with an emergency cesarean section. 29 Similarly, in our model, maternal BMI < 25 kg/m 2 at delivery significantly increased the probability of vaginal birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 25 In many studies, maternal overweight and obesity were significantly associated with a higher risk of cesarean delivery, particularly in low- and middle-income countries. 3 , 20 , 28 , 29 In high-income countries (eg, Europe, Central Asia, and South Asia), a BMI ≥ 25 kg/m 2 was associated with an emergency cesarean section. 29 Similarly, in our model, maternal BMI < 25 kg/m 2 at delivery significantly increased the probability of vaginal birth.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 20 , 28 , 29 In high-income countries (eg, Europe, Central Asia, and South Asia), a BMI ≥ 25 kg/m 2 was associated with an emergency cesarean section. 29 Similarly, in our model, maternal BMI < 25 kg/m 2 at delivery significantly increased the probability of vaginal birth. Additionally, the pattern of overweight and obesity differs between ethnicities, countries, regions, and the level of income.…”
Section: Discussionmentioning
confidence: 99%
“…One additional paper was identified for full‐text assessment through searching reference lists of included studies, resulting in full‐text assessment being carried out on 54 papers in total. Twenty‐one papers were included in the final review and analysis 28–48 . Figure 1 illustrates the selection process, the number of studies identified and excluded at each stage, and the reasons for exclusion, in line with the PRISMA 2020 statement 49 .…”
Section: Resultsmentioning
confidence: 99%
“…There is strong evidence which suggests that maternal pre-pregnancy overweight and obesity increases the probability of caesarean delivery [14,34,35]. Moreover, overweight, and obese women who had a caesarean section experienced more adverse outcomes when compared to normal weight women with a caesarean section or obese women with a vaginal delivery [36].…”
Section: Discussionmentioning
confidence: 99%